Measuring efficiency and productivity changes: A non-parametric analysis of Ghanaian life insurance industry - Albert Ayi Ashiagbor; Raymond Dziwornu; Aku Vivian Gbade; Kwasi Offei-Kwafo; Gagakuma Liticia (Cogent Economics & Finance, 2023)
Efficiency and productivity measurement in the insurance industry has attracted great interest from academicians, practitioners, financial market analysts, insurance regulators, and researchers; however, the near absence of empirical work on the productivity changes of the life insurance industry in Ghana poses management challenges. The main objective of this paper is to measure the efficiency and productivity changes in the life insurance industry in Ghana. The Ghana National Insurance Commission's annual report data was used in this study. We employ the non-parametric Malmquist productivity change indices and the bootstrap technique to measure the productivity changes of a sample of 19 out of 20 Ghanaian life insurance firms for the period 2015-2020. The empirical results show that the level of output-oriented technical inefficiency of the life insurance industry in Ghana is approximately 17% over the period 2015-2020. This result provides us with a general guide to identify the periods in which the industry is most and least technically efficient. Also, our findings show that the estimate of total productivity changes has retrogressed about 13% over the period in the Ghanaian life insurance industry. We further identified that the deterioration in the productivity is due to efficiency changes. The decomposition of the technological changes also reveals that the life insurance industry did not benefit from pure scale efficiency. This study contributes by encouraging the policy makers and managers of life insurance firm to use scarce resources efficiently and productively in order to stay in business.
Keywords: 330; Bootstrap; Ghana; life insurance firms; Malmquist productivity; technical efficiency